Analytical Study of Donor's Milk Bank Macronutrients by Infrared Spectroscopy. Correlations With Clinic-Metabolic Profile of 100 Donors - Sbrizzi, Stefania; Quitadamo, Pasqua Anna; Ravidà, Domenico; Palumbo, Giuseppina; Cristalli, Pier Paolo; Pettoello-Mantovani, Massimo (Frontiers in Public Health, 2019)
For its specific qualitative characteristics human donor milk (DM) is the main alternative to preterm infants nutrition and growing. How several studies suggest child’s physical and mental development is influenced by breastfeeding that prevents the necrotizing enterocolitis (NEC), retinopathy of prematurity (ROP) and sepsis common in preterm newborns. Our research was conducted in NICU’s Human Milk Bank (HMB) “Allattiamolavita”. Our study was based on macronutrients analysis (MA) of 100 DM samples taken until 10 days since childbirth and analyzed by spectroscopic infrared innovative method (MIRIS). This is a specific method to analyse fat (F), crude proteins (CP), true proteins (TP), carbohydrate (CHO) and total solids (TS). We also analyzed the 100 donors’ clinic-metabolic profile by blood tests (PMT). Both data was collected between September 2015 and February 2018. The research was structured in two parts. In the first part we compared PMT with qualitative and quantitative characteristics of MA while in the second one we studied every DM macronutrient finding furthermore possible relations between them. Statistical Package for Social Sciences (SPSS-IBM 24) was used to compare data and reporting coefficient of determination using Spearman’s Rho and Kendall’s Tau. We also analyzed samples using Kolmogorov–smirnov test, Student-T test, ANOVA, Whitney U test and chi-square test. Statistically significant correlations were noted between maternal serum proteins and CP -TP of DM. The research showed also significant correlations between azotaemia and TP and an inverse correlation between serum creatinine and CP. No statistically significant correlation was observed between donors’ glycaemia and CHO. Mineral concentrations of DM emerged independent of blood minerals ( P, Ca, Fe, Na). We also calculated a normal range for individual macronutrient of human transitional milk (TM) that was not established in literature yet. Our experience allowed us to underline that human milk is a privileged site compared to donors’ clinical and metabolic disorders. Our analysis showed the major role of the HMB to provide DM to improve clinical status, growing and neurocognitive short and long term outcome of preterm infants.